2015
DOI: 10.1016/j.fertnstert.2015.07.180
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence against use of PGS in poor prognosis patients: report of normal births after transfer of embryos reported as aneuploid

Abstract: Groups presented similar pregnancy (36.2% x 31.2%; p¼0.385) and multiple pregnancy rates (31.1% x 25.0%; p¼0.541).CONCLUSIONS: Limiting the number of embryos transferred can benefit the bottom line by decreasing the incidence of multiple pregnancy. We hypothesized that patients who failed in fresh eSET could present worst prognosis and hence had lower multiple pregnancy rates in a second attempt with two embryos transferred. However, in this sample, the second transfer with two elective embryos, after a failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 0 publications
0
36
0
1
Order By: Relevance
“…Eight pregnancies (positive hCG testing) with six singleton full-term infants resulted in this group and all babies were confirmed to have a normal karyotype. Gleicher et al (2015) also reported the birth of 3 normal neonates after transfer of Baneuploid embryosŝ uggesting that abnormal cell lines seen in the blastocyst stage may segregate to the trophectoderm and thus be ultimately absent from the fetus [35]. Of note, the authors did not discuss the platforms on which the determination of aneuploidy was made.…”
Section: Technological Failurementioning
confidence: 99%
“…Eight pregnancies (positive hCG testing) with six singleton full-term infants resulted in this group and all babies were confirmed to have a normal karyotype. Gleicher et al (2015) also reported the birth of 3 normal neonates after transfer of Baneuploid embryosŝ uggesting that abnormal cell lines seen in the blastocyst stage may segregate to the trophectoderm and thus be ultimately absent from the fetus [35]. Of note, the authors did not discuss the platforms on which the determination of aneuploidy was made.…”
Section: Technological Failurementioning
confidence: 99%
“…While in our study we used NGS [5], Huang et al [1] did not. These different platforms may explain the rather low mosaicism rate in the study by Huang et al, as compared to that of others [2][3][4][5].…”
Section: Dear Editormentioning
confidence: 64%
“…Discordance among the four pieces occurred in eight out of the 51 blastocysts (15.7%). One blastocyst was discordant between the ICM and the other three TE pieces, and seven blastocysts were discordant between one of TE and the other three biopsied pieces.Previous studies of multiple TE biopsies have reported significant higher levels of false-positive diagnoses, up to 50% divergence between biopsies of the same embryos in the same laboratories and up to approximately 80% divergence between multiple biopsies in different laboratories [2][3][4]. Moreover, surprisingly, our recently published study, which used the same design as that of Huang et al, went unnoticed.…”
mentioning
confidence: 63%
“…Mosaic embryos, which are comprised of both euploid and aneuploid cells, are difficult to identify as such, and when they are identified, they are traditionally not transferred because of their ambiguous viability [13]. Nonetheless, such embryos may remain the sole recourse for transfer in patients with very poor fertility prognoses [14]. The published literature suggests that older women do not benefit from PGS, and this makes sense in that most embryos in these patients will be aneuploid and additional screening seems somewhat redundant [15,16].…”
Section: Introductionmentioning
confidence: 99%